Biofilm-based delivery approaches and specific enrichment strategies of probiotics in the human gut. (31st December 2022) - Gao, Jie; Sadiq, Faizan Ahmed; Zheng, Yixin; Zhao, Jinrong; He, Guoqing; Sang, Yaxin
ABSTRACT: The use of probiotics has been one of the effective strategies to restructure perturbed human gut microbiota following a disease or metabolic disorder. One of the biggest challenges associated with the use of probiotic-based gut modulation strategies is to keep the probiotic cells viable and stable during the gastrointestinal transit. Biofilm-based probiotics delivery approaches have emerged as fascinating modes of probiotic delivery in which probiotics show significantly greater tolerance and biotherapeutic potential, and interestingly probiotic biofilms can be developed on food-grade surfaces too, which is ideal for the growth and proliferation of bacterial cells for incorporation into food matrices. In addition, biofilms can be further encapsulated with food-grade materials or with bacterial self-produced biofilms. This review presents a newly emerging and unprecedently discussed techniques for the safe delivery of probiotics based on biofilms and further discusses newly emerging prebiotic materials which target specific gut microbiota groups for growth and proliferation.